Juramento para graduados. El producto de una reflexión colectiva - Tauro, Norma; Musso, Carlos; Argibay, Pablo; Ceriani Cernadas, José María; Pace, Rosa Angelina; Rosso, Victoria (Revista del Hospital Italiano de Buenos Aires, 2007)
-